If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -5 = -35 Reorder the terms: -5 + 15x = -35 Solving -5 + 15x = -35 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 15x = -35 + 5 Combine like terms: -5 + 5 = 0 0 + 15x = -35 + 5 15x = -35 + 5 Combine like terms: -35 + 5 = -30 15x = -30 Divide each side by '15'. x = -2 Simplifying x = -2
| 5=-3+4x-4 | | 5x-logx=1.62 | | 2(3.14)(3)(7.5)= | | x-9sqrt(x)+14=0 | | 11.2+x-7.6=4.3 | | 2(3.14)(4)(6.5)= | | 3=3x+40 | | 6=6k-5k | | (x+2)(3x+10)=3(m+5)+15 | | x+4sqrt(x)-12=0 | | 9g+5= | | X-9+5x-27=180 | | 356+56+x=-832 | | 0=1-2r-5 | | 6x^2-27y=0 | | 2/9=x/7 | | 14+19=195x | | N/15=2/3 | | 6=5p+p | | 5(x-8)+3x= | | N*6.7=268 | | 3a+8c=43 | | 13x+40=4x+5 | | 7.6a-9.6=1.2a | | 1,-10;m=1/2 | | (2)/(5)y-5=(1)/(3)y | | 4.93-9.2v=.66 | | https://s3.amazonaws.com/engradepro-myfiles/4099999686266948/sa027-2.jpg | | -(2g-6)=18 | | 8k-4=3k+6 | | 25-3x+2=-2x+17 | | 16p-2p+5p-9p+2=12 |